(untitled) - Eudes Euler de Souza Lucena; Ana Claudia de Queiroz Castro; Danielle Bezerra de Farias; Pérola Teixeira de Lima; Éricka Janine Dantas da Silveira; Kenio Costa de Lima (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Ephelides are small hyperpigmented macules common in the skin, presenting as areas with increased melanin production. Ephelides are observed in genetically predisposed individuals, particularly fair-skinned people highly susceptible to sunburn. OBJECTIVES: This study aimed to determine the prevalence of lip and perioral ephelides in 362 beach workers in the city of Natal (Rio Grande do Norte) and to investigate potential associations with sociodemographic, occupational and general health. METHODS: For this purpose clinical tests were performed by calibrated examiners in the epidemiological area around the lips and the area bounded laterally by the nasolabial groove and at the bottom by the chin. A questionnaire was completed and assessed. The possible associations between sociodemographic variables, occupational and general health with the presence of lip and perioral ephelides were evaluated by chi-square test for a significance level of 5%. RESULTS: Approximately one third of the workers were affected by perioral ephelides (33.7%) and around a quarter of them by lip ephelides (24.0%). Gender was the only variable significantly associated with the presence of perioral ephelides (p = 0.002), unlike lip ephelides which proved to be significantly associated with habits (p = 0.036) and alcoholism (0.030). CONCLUSIONS: The prevalence of ephelides in lip and perioral region was high in the study population, with gender and certain habits associated with its occurrence. FUNDAMENTOS: Efélides são máculas hiperpigmentadas pequenas, comuns na pele, que constituem uma área com maior aumento da produção de melanina. São observadas em indivíduos geneticamente predispostos, de pele clara, com grande suscetibilidade a queimaduras solares. OBJETIVOS: Esse estudo teve o propósito de verificar a prevalência de efélides labiais e periorais em 362 trabalhadores de praias do município de Natal/RN e investigar potenciais associações com variáveis sociodemográficas, ocupacionais e de saúde geral. MÉTODOS: Para tanto, foram realizados exames clínicos por examinadores calibrados, na área correspondente aos lábios e na área delimitada lateralmente pelo sulco nasolabial e inferiormente pelo mento, além de preenchimento de questionário validado. As possíveis associações das variáveis sociodemográficas, ocupacionais e de saúde geral com a presença de efélides labiais e periorais foram avaliadas pelo teste do qui-quadrado para um nível de significância de 5%. RESULTADOS: Aproximadamente um terço dos trabalhadores foi acometido por efélides perioral (33,7%) e um quarto por efélides labial (24,0%). O gênero foi a única variável que se mostrou associada significativamente com a presença de efélides periorais (p=0,002), ao contrário das efélides labiais que mostrou-se associada significativamente com hábito (p=0,036) e etilismo (0,030). CONCLUSÕES: Conclui-se que a prevalência de efélides em região perioral e labial foi elevada na população estudada e o gênero e hábitos foram associadas à sua ocorrência.